AÇÃO DE REGULADORES VEGETAIS EM COLZA (Brassica napus L.) - Castro, Paulo R. C.; Evangelista, Edison S.; Melotto, Eunice; Rodrigues, Efraim (REVISTA DE AGRICULTURA, 2015)
AÇÃO DE REGULADORES VEGETAIS EM COLZA (Brassica napus L.)